Književnost globalizacije ili globalizacija književnosti? - Majić, Ivan, kroatist (Array, 2009)
Influence of contemporary globalization processes forces all cultural products to re-examine their positions. Literature along with literary theory and comparative literature are no exception to this occurrence. This article aims to foresee what story about literature will be told as a result both of new type of dominance embodied in English language and unforeseeable yet immense reception possibilities via digital media. Methodological issues that have become more apparent in the last decades are a sign of change in terms of literature perception. Along these lines the emergence of postnational, postcolonial, and inter/transcultural approaches to literature analysis can be viewed, as these take identity to be a non-fixed category and almost exclusively an alternative and/or a hybrid.